PERBANDINGAN KEJADIAN KONTAMINASI TELUR CACING SOIL TRANSMITTED HELMINTHES PADA SAYUR KANGKUNG (Ipomoea aquatica) YANG DIJUAL DI PASAR TRADISIONAL DAN PASAR MODERN DI KOTA MEDAN - ASTRI NOVIA RIZQI; NELLI MURLINA (LP2MTBM MAKARIOZ, 2023)
Vegetables have the potential to be a source of transmission of Soil Transmitted Helminth (STH) through soil used in vegetable cultivation and water is an important transmission medium. The incidence of STH contamination in the city of Medan is still quite high, one of the main routes of transmission of STH contamination is through consumption of contaminated vegetables such as kale. To compare the incidence of STH worm egg contamination in kale (Ipomoea Aquatica) which is sold in traditional and modern markets in Medan. The research design used was analytic observational with a cross-sectional study. The sample used in this study amounted to 140 samples. Kale vegetables were taken from 70 samples from traditional markets and 70 samples from modern markets in 21 sub-districts in the city of Medan. Then the samples were examined in the parasitology laboratory of the University of Muhammadiyah North Sumatra (UMSU) using the sedimentation method and safranin staining. Then the data is processed with the SPSS program. From 140 samples of kale, 28 samples from traditional markets were positive for STH contamination (73.68%) and 10 samples from modern markets were positive for STH contamination (35.71%). The types of STH found were Ascaris lumbricoides (13.15%) and Hookworm (86.84%). Based on the results of this study, it can be concluded that there is a significant difference in STH contamination in kale which is sold in traditional markets and in modern markets in the city of Medan as evidenced by the p-value obtained, which is 0.001 (p <0.005). Keywords: Soil Transmitted Helminthes, Water Spinach Which, Traditional Market, Modern Market